Spontaneous central vein thrombosis in a patient with activated protein C resistance and dengue infection: An association or causation? - Tanmoy Ghatak; Ratender K Singh; Arvind K Baronia (Wolters Kluwer Medknow Publications, 2013)
Spontaneous central vein thrombosis is a rare and potentially fatal condition in critical care setting. Activated protein C resistance due to homozygous factor V Leiden mutation is an exceptional cause of central venous thrombosis. We recently treated a healthy female student who presented with acute febrile illness, septic shock, and encephalopathy. Neck ultrasonography (USG) prior to an attempt of right internal jugular vein (IJV) cannulation revealed non compressibility of the vein along with absence of venous blood flow. Right IJV and subclavian vein thrombus was confirmed subsequently in USG Doppler by radiologist. Radiological evidence of distal pulmonary artery embolism in pulmonary angiography was also evident. Further investigations demonstrated homozygous Factor V Leiden mutation and activated factor C resistance and Dengue IgM positivity in our patient. Intravenous heparin followed by oral vitamin K anticoagulants (OVKA) aided in her recovery. Spontaneous intravascular thrombosis with activated protein C resistance and the relationship of acute Dengue infection were explored in our report.